2007
DOI: 10.1158/1055-9965.epi-07-0227
|View full text |Cite
|
Sign up to set email alerts
|

Similar Exposure to a Tobacco-Specific Carcinogen in Smokeless Tobacco Users and Cigarette Smokers

Abstract: Smokeless tobacco has been proposed as a reduced risk substitute for smoking, but no large studies have investigated exposure to the powerful carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in smokeless tobacco users versus smokers. The purpose of this study was to carry out such a comparison. Levels of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol and its glucuronides (total NNAL), a biomarker of NNK exposure, and cotinine, a biomarker of nicotine exposure, were quantified in the urine of 420 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
69
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 29 publications
14
69
0
2
Order By: Relevance
“…22 Although TSNA levels in snus on the Swedish market have been greatly reduced since the 1980s, 23 the prerequisites for carcinogenicity are indisputably present. A recent report from the United States 24 provides evidence that users of smokeless tobacco may be exposed to NNK to a similar degree as are smokers. And others have shown that differences in current TSNA levels between American and Swedish moist snuff may not be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…22 Although TSNA levels in snus on the Swedish market have been greatly reduced since the 1980s, 23 the prerequisites for carcinogenicity are indisputably present. A recent report from the United States 24 provides evidence that users of smokeless tobacco may be exposed to NNK to a similar degree as are smokers. And others have shown that differences in current TSNA levels between American and Swedish moist snuff may not be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of NNN and NNK in Swedish products are lower than those in brands sold in the United States, but the total amounts are still about 1-2 ppm, approximately 1000 times higher than levels of carcinogenic nitrosamines found in cured meats or beer, which are the consumer products most commonly contaminated with such compounds. We have recently completed a study in which we compared levels of total NNAL in the urine of 182 American smokeless tobacco users and 420 smokers (113). The results demonstrated that total NNAL levels were similar in the urine of smokeless tobacco users and smokers.…”
Section: The Second Re-emergence Of Smokeless Tobaccomentioning
confidence: 99%
“…The previous literature states that beedis contain much higher levels of phenol, hydrogen cyanide, benzo(a)pyrene and flavouring agents than conventional cigarettes and it may produce carcinogens other than those commonly found in tobacco [10]. Flavouring agents added to beedis are not rigidly controlled and so the composition may vary [13].…”
Section: Discussionmentioning
confidence: 99%